DESAIN EVALUASI KURIKULUM PENDIDIKAN DAN PELATIHAN (DIKLAT) (Studi kasus di Unit Pelaksana Teknis Dinas (UPTD) Balai Latihan Kerja Dinas Tenaga Kerja dan Transmigrasi Kota Probolinggo) - Rofika Nuriyanti (STKIP PGRI TULUNGAGUNG, 2018)
The purpose of this research is to describe and know the design evaluation of education and training curriculum at UPTD Balai Latihan Kerja Dinas Tenaga Kerja dan Transmigrasi Kota Probolinggo. This research method uses descriptive qualitative researchÂ with case study design. This research uses snow ball sampling technique. The result of thisÂ is found three evaluation design that is 1) evaluation of training participant, 2) evaluation of instructor, and 3) evaluation of training organizer. The thing has to be attended in the training curriculum are; type of evaluation, tool / instrument of evaluation, time of evaluation implementation, who conducts evaluation. Evaluation is a important thing to do starting from the early stages of the implementation of the training until the end of the training program activities.KeyWords: Design, Â evaluation, curriculum, education and training.